You go first - Kelly, Erin Entrada 1977- (Greenwillow Books, an imprint of HarperCollinsPublishers, 2018)
Charlotte, twelve, and Ben, eleven, are highly-skilled competitors at online Scrabble and that connection helps both as they face family issues and the turmoil of middle school